Self-supporting low-platinum nano high-entropy alloy electrode and high-performance fuel cell membrane electrode prepared from same

By using a self-supported low-platinum six-member nano high-entropy alloy electrode in fuel cell membrane electrodes, the problems of high platinum load, poor anti-toxicity and insufficient stability in existing membrane electrodes are solved, and more efficient and more Economical fuel cell performance and extend the service life of membrane electrodes.

CN119481109APending Publication Date: 2025-02-18LANZHOU JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411599148.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The high loading of platinum, poor anti-toxicity and insufficient long-term stability in existing fuel cell membrane electrodes limits its large-scale application and service life.

Method used

A self-supported low-platinum six-membered nano-high entropy alloy electrode is prepared by reaction in an autoclave, combined with a porous conductive substrate to form a high-performance membrane electrode. This design improves the stability and anti-toxicity properties of the electrode by optimizing the amount and structure of platinum.

Benefits of technology

It significantly reduces the amount of platinum, improves the stability and anti-toxicity of the membrane electrode, extends the service life, optimizes the contact conditions of the three-phase interface, and improves the overall performance and economy of the fuel cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005127800140000011
    Figure HDA0005127800140000011
  • Figure HDA0005127800140000012
    Figure HDA0005127800140000012
  • Figure HDA0005127800140000013
    Figure HDA0005127800140000013
Patent Text Reader

Abstract

The invention belongs to the field of fuel cells, and provides a preparation method of a self-supporting low-platinum six-element nano high-entropy alloy electrode and a high-performance fuel cell membrane electrode constructed by the self-supporting low-platinum six-element nano high-entropy alloy electrode. The membrane electrode comprises high-entropy active metal, a porous conductive substrate and an anion exchange membrane, and the precious metal loading capacity of the membrane electrode is smaller than or equal to 5%. Compared with the prior art, the preparation method has the advantages that through the structural design of the self-supporting electrode of the uniformly distributed six-element high-entropy nano-alloy, the electrochemical stability of the membrane electrode is remarkably improved, and the membrane electrode can show higher poison resistance and is suitable for various fuel cells; the self-supporting structure optimizes the mass transfer characteristic of a three-phase interface under the condition of no high polymer adhesive, so that active sites are tightly attached to the carrier, the overall conductivity and stability of the electrode are improved, and the catalytic efficiency of the membrane electrode is improved; especially under a low platinum condition, the service life of the membrane electrode is prolonged, the cost of the membrane electrode is greatly reduced, and wide application of the fuel cell in a sustainable energy system is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of membrane electrode materials for fuel cells. The invention introduces a membrane electrode prepared based on high entropy alloy nanomaterials and its application in fuel cells. Background Art

[0002] The membrane electrode is the core component of the fuel cell, and its performance directly affects the overall electrochemical efficiency, output power and stability of the fuel cell. The membrane electrode consists of a three-layer structure: a catalyst layer, an anion exchange membrane and a gas diffusion layer. Among them, the main task of the catalyst layer is to catalyze the redox reaction, the anion exchange membrane is responsible for conducting anions and isolating the fuel and the oxidant, and the gas diffusion layer ensures the uniform distribution of the reaction gas and the removal of water. Platinum-based catalysts are widely used in traditional membrane electrodes. Due to their superior catalytic activity, they are considered to be ideal materials for oxygen reduction and fuel oxidation reactions. However, the high cost of platinum and the scarcity of global reserves limit its large-scale application. In addition, platinum catalysts are easily poisoned by intermediates such as carbon monoxide in the fuel during operation, resulting in a decrease in catalytic activity, which significantly affects the performance and service life of the fuel cell. The key to solving these problems lies in the development of new catalytic electrodes to reduce the amount of platinum and enhance the anti-poisoning ability and stability of the catalyst, thereby improving the economy and durability of the membrane electrode.

[0003] High entropy alloys are a new type of alloy material composed of multiple (usually five or more) metal elements in nearly equimolar ratios. They have attracted widespread attention for their complex solid solution structure and significant synergistic effect. Due to the mixing effect of multiple elements, high entropy alloys exhibit excellent performance in lattice stability, corrosion resistance and oxidation resistance, and are suitable for a variety of extreme environments. In electrocatalytic applications, high entropy alloys can significantly improve the activity and selectivity of electrocatalytic reactions due to their highly tunable electronic structure and rich surface chemical sites. The presence of multiple active sites provides multi-path reaction channels, allowing high entropy alloys to not only cope with complex reaction mechanisms, but also maintain efficient catalytic performance under conditions containing impurities. Compared with traditional platinum-based or binary and ternary alloy catalysts, platinum-based high entropy alloys have significant advantages in anti-poisoning, corrosion resistance and durability, and have great potential in the application of clean energy technologies such as fuel cells.

[0004] The present invention proposes a novel self-supporting low-platinum six-element nano high-entropy alloy electrode, which is used to construct a high-performance fuel cell membrane electrode, aiming to cope with the challenges of high platinum loading, poor anti-poisoning ability and insufficient long-term stability faced by existing fuel cell membrane electrode technology. The invention adopts a self-supporting low-platinum six-element nano high-entropy alloy as a catalytic electrode, which improves the stability and anti-poisoning performance of the electrode under low platinum loading. The introduction of multiple metals ensures the uniform distribution and good adhesion of the catalyst on the electrode, enhances the conductivity and mechanical strength of the electrode, and provides a more open and uniform environment for the three-phase interface, thereby optimizing the contact conditions of the gas, liquid and solid phases. The optimized three-phase interface can significantly improve the contact efficiency between the reactants and the catalytic active sites and reduce the mass transfer resistance. This design increases the effective mass transfer channel in the electrode, promotes the penetration and diffusion of the electrolyte solution in the electrode, ensures that the reaction products can be quickly discharged from the reaction zone, and maintains the continuity and stability of the electrochemical reaction. This design not only improves the economy of the fuel cell by optimizing the amount of platinum used, but also significantly extends the service life and overall performance of the membrane electrode by virtue of its high stability and durability. This breakthrough provides strong support for achieving lower-cost and more efficient clean energy solutions, and opens up a new path for the future development of fuel cell technology. Summary of the invention

[0005] The purpose of the present invention is to propose a method for preparing a high-performance fuel cell membrane electrode in view of the above problems. The method uses alloying as a route and relies on a porous conductive substrate, and has the advantages of simple process, low cost, high catalytic efficiency, and low energy consumption in the production process. The method prepares a high-performance fuel cell membrane electrode with excellent catalytic performance, good durability, and low surface platinum loading.

[0006] To achieve the above object, the present invention adopts the following scheme:

[0007] 1. Preparation of high-performance fuel cell membrane electrode

[0008] (1) Preparation of self-supporting low-platinum hexavalent nano-high entropy alloy electrodes

[0009] The six metal salts are evenly dispersed in a dispersant, and a reducing agent and a pretreated porous conductive substrate are added and placed in a high-pressure reactor for reaction. The reaction time is 3 to 12 hours. After the reaction is completed, a self-supporting low-platinum hexavalent nano-high-entropy alloy electrode is obtained by washing and drying.

[0010] The metal salts are six kinds of platinum salts including copper acetylacetonate, molybdenum acetylacetonate, manganese acetylacetonate, nickel acetylacetonate, iron acetylacetonate, cobalt chloride, nickel chloride, copper acetate, iron chloride, platinum acetylacetonate, platinum chloride and manganese chloride, and the molar fraction of each salt ranges from 0.8 to 5.0%, and the total loading amount is 5 to 30%.

[0011] The dispersant is one or more of oleylamine, oleic acid and stearic acid.

[0012] The reducing agent is one of glucose, sodium borohydride and ascorbic acid, and the amount of the reducing agent added is 1 to 3 times the amount of the metal salt substance.

[0013] The pretreatment operation is 1 to 3 mol L -1 Sulfuric acid solution for 2 to 24 hours.

[0014] The porous conductive substrate is one of carbon fiber cloth, carbon paper, carbon felt, graphene-reinforced carbon cloth, and hydrophilic porous carbon cloth.

[0015] The reaction in the high pressure reactor is carried out at 5-15°C min -1 The temperature is raised to 150-300℃ at a rate of 1-10℃ / min. -1 The mixture was cooled to room temperature at a rate of 100 °C and finally washed with anhydrous ethanol for 3 to 5 times and dried in a vacuum at 60 to 80 °C for 12 to 24 h.

[0016] (2) Preparation of high-performance fuel cell membrane electrode

[0017] The anion exchange membrane is pretreated, washed and dried, and then the obtained self-supporting low-platinum hexavalent nano-high entropy alloy electrode is assembled with the anion exchange membrane. Finally, the membrane electrode assembly is placed in a hot pressing device, and uniform positive pressure is applied at high temperature to obtain a high-performance fuel cell membrane electrode.

[0018] The anion exchange membrane is one of a polybenzimidazole membrane, a perfluorosulfonic acid anion exchange membrane or a sulfonated polyarylether membrane.

[0019] The anion exchange membrane pretreatment method is alkali treatment, which is to immerse the anion exchange membrane in 0.5-1 mol L -1 NaOH solution for 4 to 12 hours, and finally dried at 25 to 50°C for 0.5 to 3 hours.

[0020] The high temperature in the hot pressing equipment is 80-150° C., the positive pressure applied is 0.5-2.0 MPa, and the positive pressure is maintained for 1-10 minutes.

[0021] 2. Characterization of high performance fuel cell membrane electrode

[0022] Taking the carbon cloth-loaded platinum-copper-molybdenum-manganese-nickel-iron hexameric nano self-supporting high-entropy alloy membrane electrode (PtCuMoMnNiFe-NPs) as an example, this material is characterized by SEM, TEM, and XRD.

[0023] (1) SEM characterization

[0024] SEM images ( Figure 2 ) revealed the microstructure of the prepared PtCuMoMnNiFe-NPs, Figure 2 a 1μm, it can be observed that the nanoparticles are relatively uniformly attached to the fibers of the porous conductive substrate, forming a highly dispersed catalyst layer. The uniform particle size and good surface coverage help to improve catalytic activity and conductivity. Figure 2 b is a SEM image of the sample at a scale of 20 nm, which further reveals the morphology and structural characteristics of the nanoparticles. The particles show an irregular agglomeration morphology and high surface roughness, which is conducive to increasing the specific surface area and the number of active sites for catalytic reactions.

[0025] (2) TEM characterization

[0026] TEM images ( Figure 3 ) also revealed the microstructure of the prepared PtCuMoMnNiFe-NPs, Figure 3 In a, at a scale of 50 nm, the aggregated structure of high entropy alloy nanoparticles was observed. Figure 3 Further zooming in to the 20 nm scale in b, the microstructure becomes clearer, showing that the high-entropy alloy nanoparticles are anchored on the porous conductive substrate, and the presence of pores and layered structure can be observed, which can significantly improve the transfer efficiency of reactants and products throughout the reaction process.

[0027] (3) XRD characterization

[0028] In order to obtain more membrane electrode information, XRD test was performed on PtCuMoMnNiFe-NPs. Figure 4 The test results are shown in Figure 2. In PtCuMoMnNiFe-NPs, diffraction peaks appear at 41.4° and 81.9°, corresponding to the (111) and (311) crystal planes of Pt, respectively, indicating the formation of an alloy. In addition, compared with the porous conductive substrate, the peak intensity increases significantly but there is no obvious peak shift, which indicates that the high entropy alloy maintains a well-preserved highly disordered state on the porous conductive substrate without obvious phase separation.

[0029] 3. Electrochemical testing of high entropy alloy membrane electrodes

[0030] In order to illustrate the performance of the prepared hexameric nano-high entropy alloy membrane electrode, the electrochemical test was carried out by assembling the PtCuMoMnNiFe-NPs membrane electrode into a direct glycerol fuel cell (DGFCs) as an example.

[0031] (1) Peak power density detection

[0032] Figure 5This is the power density test result of the PtCuMoMnNiFe-NPs membrane electrode prepared in the present invention catalyzing the electro-oxidation of propylene glycol.

[0033] The specific method of the power density test is to use the PtCuMoMnNiFe-NPs membrane electrode as the anode, the platinum sheet as the cathode, the Ag / AgCl electrode as the reference electrode, and a propylene glycol and oxygen supply system to construct a fuel cell test device to achieve the power density measurement of the actual fuel cell stack.

[0034] It can be seen that the open circuit voltage (OCV) of the prepared membrane electrode is 0.93 V. Generally speaking, a higher OCV indicates a significantly lower polarization overpotential in DGFCs. More importantly, the peak current density of PtCuMoMnNiFe-NPs is 54.56 mA cm at an overpotential of -0.077 V. -2 , at 0.075A cm -2 The maximum power density is 29.99 mW cm -2 , indicating that the PtCuMoMnNiFe-NPs membrane electrode has good catalytic activity.

[0035] (2) Durability testing

[0036] Stability is also one of the important parameters to measure the catalytic performance of the electrode. Therefore, the stability test of PtCuMoMnNiFe-NPs membrane electrode was carried out ( Figure 6 ).

[0037] The specific method of the stability test is to use the PtCuMoMnNiFe-NPs electrode as the working electrode, the platinum sheet as the counter electrode, the Ag / AgCl electrode as the reference electrode and 1M KOH solution to construct a three-electrode electrochemical workstation, and operate for 3000s at an applied voltage of -0.2V.

[0038] It can be seen that the accumulation of catalytic intermediates rapidly reduces the current density on the electrode. However, the retained current density (0.0995 mA cm) of PtCuMoMnNiFe-NPs was - 2) is the initial current density (0.1207 mA cm - 2) is 82.4%, indicating that the catalytic electrode has good catalytic stability.

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] 1. The membrane electrode of the present invention significantly reduces the amount of platinum while maintaining excellent catalytic activity, greatly reduces the manufacturing cost of fuel cells, and meets the needs of green and efficient development.

[0041] 2. The present invention innovatively uniformly loads the hexavalent high entropy alloy material on a porous conductive substrate to construct a stable three-phase interface structure. The membrane electrode exhibits significant electrochemical stability and stronger anti-poisoning ability in long-term operation and multiple cycle tests, thereby extending the service life of the membrane electrode.

[0042] 3. The present invention adopts a self-supporting structure design, so that the high entropy alloy catalyst material can be firmly bonded to the porous conductive substrate without additional adhesives. This design improves conductivity and reaction efficiency, simplifies the preparation process and reduces mass transfer resistance, thereby enhancing the reliability and consistency of the overall performance of the membrane electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 This is a photo of the membrane electrode assembled with the low-platinum hexameric nano-high entropy alloy prepared by the present invention in a fuel cell.

[0044] Figure 2 SEM images of the best-performing PtCuMoMnNiFe-NPs prepared in the present invention, 1 μm (2a); 20 nm (2b).

[0045] Figure 3 TEM images of PtCuMoMnNiFe-NPs with the best performance prepared by the present invention, 20nm (3a); 5nm (3b).

[0046] Figure 4 This is the XRD spectrum of PtCuMoMnNiFe-NPs prepared in the present invention.

[0047] Figure 5 The power density of the best-performing PtCuMoMnNiFe-NPs prepared by the present invention is tested under different loads.

[0048] Figure 6 The stability test of the best-performing PtCuMoMnNiFe-NPs prepared by the present invention at -0.2V. DETAILED DESCRIPTION

[0049] The preparation of the self-supporting low-platinum hexa-element high-entropy alloy membrane electrode and the electro-oxidation performance of propylene glycol of the present invention are further described below through specific examples and comparative examples.

[0050] Example 1

[0051] (1) Pretreatment of hydrophilic porous carbon cloth: 10 portions of hydrophilic porous carbon cloth cut into 1 cm × 1 cm pieces were placed in 50 mL of 2.3 mol L -1The carbon cloth substrate is placed in a sulfuric acid solution, stirred for 5 minutes, and then allowed to stand for 12 to 24 hours, and the carbon cloth substrate is taken out and washed with deionized water for 3 to 5 times to obtain a pretreated hydrophilic porous carbon cloth;

[0052] (2) Preparation of a metal precursor solution: Based on the amount of substance, using oleylamine as a solvent, one part of platinum acetylacetonate, one part of copper acetylacetonate, one part of molybdenum acetylacetonate, one part of manganese acetylacetonate, one part of nickel acetylacetonate and one part of iron acetylacetonate are mixed and added into 10 mL of oleylamine, and stirred for 5 hours to make the solution uniform, thereby preparing a metal precursor solution;

[0053] (3) Preparation of carbon cloth-supported Pt-Cu-Mo-Mn-Ni-Fe hexavalent high entropy alloy catalytic electrode: The pre-treated hydrophilic porous carbon cloth and six portions of glucose were added to the metal precursor solution. The mixture was then placed in a high-pressure reactor for high-temperature reaction (5°C min -1 The heating rate was raised to 200 °C and kept constant for 5 h, and then the temperature was raised to 10 °C min -1 After cooling to room temperature at a rate of , the carbon cloth substrate was taken out, washed with anhydrous ethanol for 3 to 5 times, and dried in vacuum at 60°C for 12 h to obtain a carbon cloth-supported Pt-Cu-Mo-Mn-Ni-Fe hexameric self-supporting high-entropy alloy electrode.

[0054] (4) Place the carbon cloth-supported Pt-Cu-Mo-Mn-Ni-Fe hexavalent self-supporting high entropy alloy material in a tube furnace for annealing at 15°C min -1 The temperature was raised to 600°C at a rate of 10°C / min and kept at this temperature for 3 h. Then the tube furnace heater was turned off and the temperature was increased to 600°C / min at a rate of 10°C / min. -1 rate to room temperature.

[0055] (5) Soak the polybenzimidazole membrane in 1 mol L -1 NaOH solution for 6 h, washed and dried at 35 °C for 2 h.

[0056] (6) Assemble the hexavalent self-supporting high-entropy alloy electrode of platinum, copper, molybdenum, manganese, nickel and iron supported by carbon cloth with the treated polybenzimidazole membrane to ensure that the electrode and the polybenzimidazole membrane are tightly attached. Then, place the membrane electrode assembly into a hot press and apply a uniform positive pressure of 1.2 MPa at 80°C for 8 minutes. Finally, a high-performance fuel cell membrane electrode is obtained.

[0057] (7) Application of catalytic oxidation of propylene glycol in fuel cells: When the prepared membrane electrode is used as the main working electrode of a direct propylene glycol fuel cell for electrocatalysis of propylene glycol, the peak power density is 29.99 mW cm after optimization. -2 , which is 2.05 times that of commercial platinum / carbon electrodes (14.61 mW cm -2 ), at a voltage of -0.2 V, after a 3000s durability test, the electrode retained a current density (0.0995 mA cm- 2) It is still higher than the retention current density of commercial platinum / carbon electrodes (0.0018 mA cm - 2), indicating that the electrode has good catalytic stability.

[0058] Example 2

[0059] The platinum acetylacetonate, copper acetylacetonate, molybdenum acetylacetonate, manganese acetylacetonate, nickel acetylacetonate and iron acetylacetonate in step (2) are adjusted to cobalt chloride, nickel chloride, copper acetate, iron chloride, platinum chloride and manganese chloride, and the other operations are the same as those in Example 1 to obtain a low-platinum hexa-element nano-high entropy alloy membrane electrode.

[0060] The prepared membrane electrode was subjected to electrochemical testing: the peak power density was 28.25 mW cm -2 , which is 1.93 times that of commercial platinum / carbon electrodes (14.61 mW cm -2 ), at a voltage of -0.2 V, after a 3000s durability test, the electrode retained current density (0.0869 mA cm - 2) It is still higher than the retention current density of commercial platinum / carbon electrodes (0.0018 mA cm - 2), indicating that the electrode has good catalytic stability.

[0061] Example 3

[0062] The proportions of one part of platinum acetylacetonate, one part of copper acetylacetonate, one part of molybdenum acetylacetonate, one part of manganese acetylacetonate, one part of nickel acetylacetonate and one part of iron acetylacetonate in step (2) are all adjusted to 0.5 parts, and the other operations are the same as those in Example 1 to obtain a low-platinum hexa-element nano-high entropy alloy membrane electrode.

[0063] The prepared membrane electrode was subjected to electrochemical testing: the peak power density was 23.74 mW cm -2 , which is 1.62 times that of commercial platinum / carbon electrodes (14.61 mW cm -2 ), at a voltage of -0.2V, after a 3000s durability test, the electrode retained current density (0.0721mAcm - 2) It is still higher than the retention current density of commercial platinum / carbon electrodes (0.0018 mA cm - 2), indicating that the electrode has good catalytic stability.

[0064] Comparative Example 1

[0065] The positive pressure applied in step (6) was adjusted to 3.5 MPa, and the other operations were the same as in Example 1. The obtained low-platinum hexa-element nano-high-entropy alloy membrane electrode did not reach the target morphology.

[0066] This is because the carbon cloth substrate was crushed due to excessive positive pressure, and the electrode collapsed before it could be tightly connected with the anion exchange membrane.

[0067] Comparative Example 2

[0068] The reaction temperature in step (3) was adjusted to 60° C., and the other operations were the same as in Example 1 to obtain a low-platinum hexavalent nano-high entropy alloy membrane electrode.

[0069] The prepared membrane electrode was subjected to electrochemical testing: the peak power density was only 7.49 mW cm -2 At a voltage of -0.2 V, after a 3000s durability test, the electrode's retained current density was only (0.0133 mA cm - 2).

[0070] This is because the reaction temperature is too low to provide sufficient energy to completely reduce the metal salt, causing part of the metal to exist as oxides or other unreduced forms, resulting in reduced purity and performance of the high entropy alloy on the membrane electrode.

Claims

1. A self-supporting low-platinum six-element nano high-entropy alloy electrode and a high-performance fuel cell membrane electrode constructed therefrom, comprising the following steps: (1) Preparation of self-supporting low-platinum hexavalent nano-high-entropy alloy electrodes: six metal salts are dispersed in a dispersant, a reducing agent and a pre-treated porous conductive substrate are added, and the electrodes are placed in a high-pressure reactor for reaction at a certain temperature for 3 to 12 hours. After the reaction is completed, the electrodes are washed and dried, and placed in a tube furnace for heat treatment under gas protection to obtain self-supporting low-platinum hexavalent nano-high-entropy alloy electrodes; (2) The anion exchange membrane is pretreated, washed and dried, and then the obtained self-supporting low-platinum hexavalent nano-high entropy alloy electrode is assembled with the anion exchange membrane. Finally, the membrane electrode assembly is placed in a hot pressing device and a uniform positive pressure is applied at a high temperature to obtain a high-performance fuel cell membrane electrode.

2. The method for preparing the self-supporting low-platinum hexa-element nano-high entropy alloy electrode according to claim 1, characterized in that: The metal salt in step (1) is six of the following: copper acetylacetonate, molybdenum acetylacetonate, manganese acetylacetonate, nickel acetylacetonate, iron acetylacetonate, cobalt chloride, nickel chloride, copper acetate, iron chloride, platinum acetylacetonate, platinum chloride, and manganese chloride, wherein the molar fraction of each salt is in the range of 0.8 to 5.0%, and the total loading is 5 to 30%.

3. The method for preparing the self-supporting low-platinum hexa-element nano-high entropy alloy electrode according to claim 1, characterized in that: The dispersant in step (1) is one or more of oleylamine, oleic acid, and stearic acid; the reducing agent in step (1) is one of hydrazine hydrate, glucose, sodium borohydride, and ascorbic acid, and the amount of the reducing agent added is 1 to 3 times the mass of the metal salt.

4. The method for preparing the self-supporting low-platinum hexa-element nano-high entropy alloy electrode according to claim 1, characterized in that: The pretreatment method of the porous conductive substrate in step (1) is acid leaching for 2 to 24 hours; the acid used in the pretreatment in step (1) is 1 to 3 molL -1 of sulfuric acid solution.

5. The method for preparing the self-supporting low-platinum hexa-element nano-high entropy alloy electrode according to claim 1, characterized in that: In step (1), the porous conductive substrate is one of carbon fiber cloth, carbon paper, carbon felt, graphene-reinforced carbon cloth, and hydrophilic porous carbon cloth.

6. The method for preparing the self-supporting low-platinum hexa-element nano-high entropy alloy electrode according to claim 1, characterized in that: The high pressure reactor reaction in step (1) is carried out at 5-15°C min -1 The temperature was raised to 150-300°C at a rate of 1-20°C / min, and the reaction was continued at a constant temperature for 3-12 hours. -1 The mixture was cooled to room temperature at a rate of 100 °C and finally washed with anhydrous ethanol for 3 to 5 times and dried in a vacuum at 60 to 80 °C for 12 to 24 h.

7. The method for preparing the self-supporting low-platinum hexa-element nano-high entropy alloy electrode according to claim 1, characterized in that: The heat treatment in the tubular furnace in step (1) is annealing treatment, which is performed at 10-30°C min -1 The temperature is raised to 300-800℃ at a rate of 1-4h, and then heated at 5-20℃min -1 rate to room temperature.

8. The method for preparing a high-performance fuel cell membrane electrode according to claim 1, characterized in that: The anion exchange membrane in step (2) is one or more of a polybenzimidazole membrane, a perfluorosulfonic acid anion exchange membrane or a sulfonated polyarylether membrane.

9. The method for preparing a high-performance fuel cell membrane electrode according to claim 1, characterized in that: The thickness of the anion exchange membrane in step (2) is 0.1 to 0.5 mm.

10. The method for preparing a high performance fuel cell membrane electrode according to claim 1, characterized in that: The anion exchange membrane pretreatment method in step (2) is alkali treatment, which is to immerse the anion exchange membrane in 0.5-1.0 mol L -1 NaOH solution for 4 to 12 hours, and finally dried at 25 to 50°C for 0.5 to 3 hours.

11. The method for preparing a high performance fuel cell membrane electrode according to claim 1, characterized in that: The hot pressing process in step (2) has a high temperature of 80 to 150° C., an applied positive pressure of 0.5 to 2.0 MPa, and a time for maintaining the applied positive pressure of 1 to 10 minutes.